The unlikely candidate : what losing an election taught me about how to change politics - Milani, Ali (Policy Press, 2022)
The COVID-19 pandemic is reshaping our politics, economy and society, providing a chance to reset and redesign politics. Ali Milani brings a unique perspective to the key political issues we're facing and inspires a new generation of political leaders from the disenfranchised, disillusioned and marginalised in society.